Primary Hyperparathyroidism: 11-Year Experience in a Single Institute in Thailand - Poramaporn Prasarttong-Osoth; Pakpong Wathanaoran; Waraporn Imruetaicharoenchoke; Supakorn Rojananin (International Journal of Endocrinology)
Primary hyperparathyroidism (PHPT) is not an uncommon disease in the western countries. In Thailand, on the contrary, PHPT was a rare condition with various clinical presentations. All 45 PHPT patients who underwent parathyroidectomy at the Department of Surgery, Siriraj Hospital during January 1997 and December 2007 were retrospectively reviewed. Demographic data, clinical presentation, localizations imaging, operative procedures, findings, complications, and pathological reports were analyzed. Median age was 49 years (range 15–89 years) with female: male ratio of 3 : 1. Only one patient (2.2%) was asymptomatic PHPT. Of all symptomatic cases, 30 (66.7%) had skeletal symptoms, 7 (15.6%) had renal impairment, and 39 (86.7%) had mixed symptoms. 42 patients (93.3%) had parathyroid scan and all had bilateral exploration of the neck. Postoperative hungry bone syndrome was noted in 10 patients (22%). On followup, skeletal and neuropsychiatric symptoms were improved but the renal impairment was remained. The s small number of asymptomatic PHPT in our study may refer to large number of underdiagnosed PHPT in general population. The guideline for screening serum calcium for diagnosis of PHPT in Thai populations will improve the long-term consequence of the disease but will need further information to identify the target group.